Star Wars: The Empire Strikes Back - George Lucas (2026)
Star Wars; The Empire Strikes Back is a 1980 American epic space opera film directed by Irvin Kershner. It is the second film in the original Star Wars trilogy and the fifth film in the Star Wars franchise.